The Associations of Emotion Coping Appraisal With Both the Cue–Outcome Contingency and Perceived Verbal Abuse Exposure - Shin, Dong Woo; Yoon, Taekeun; Jeong, Bumseok (Frontiers in Psychiatry, 2019)
Previous studies have reported an association between verbal abuse in early childhood and structural and functional alterations in the young adult brain, supporting the existence of critical periods in human brain development. In addition, exposure to verbal abuse in early childhood is strongly correlated with lifetime psychiatric illness. Resilience is defined as the ability to avoid the negative psychological, biological, and social consequences of stress that impair psychological and physical homeostasis and is used to cope with these psychiatric diseases. We attempted to explain the mediatable present function of resilience and its associations with several psychiatric disorders, with verbal abuse exposure in early childhood and with the present value of the readily measurable and conceptually connected generative Bayesian model parameter. Thirty-six subjects performed a cross-modal associative learning task requiring them to learn the predictive strength of auditory cues and predict a subsequent visual stimulus. The probability of the association changed across each trial block. Subjects’ responses were modelled as a hierarchical Bayesian belief-updating process using a hierarchical Gaussian filter (HGF) with three levels, a Sutton K1 model, and Rescorla-Wagner model. Subjects completed the Korean version of the Verbal Abuse Questionnaire (VAQ) for segmented periods (aged 0 to 6, 7 to 12, and 13 to 18 years), and their positive self-appraisal was estimated using the Resilience Appraisal Scale (RAS). Random-effects Bayesian model selection identified HGF as the best model. Of the VAQ values for specific periods, only preschool VAQ scores were negatively correlated with RAS scores. The tonic volatility parameter, omega 2, of HGF showed a negative relationship with RAS emotion coping scores. The linear regression model explained 18.3% of the variance of emotion coping appraisal with omega 2 and preschool VAQ scores. Based on the results obtained from young adults, decrease in emotion coping appraisal can be explained by an increase in the number of experiences of verbal abuse in early childhood and the increased tendency to update beliefs about the cue-outcome associative probability in a volatile environment.